Hippocampal atrophy has limited usefulness as a diagnostic biomarker on the early onset Alzheimer's disease patients: A comparison between visual and quantitative assessment - Falgàs, Neus; Sánchez-Valle, Raquel; Bargalló, Núria; Balasa, Mircea; Fernández-Villullas, Guadalupe; Bosch, Beatriz; Olives, Jaume; Tort-Merino, Adrià; Antonell, Anna; Muñoz-García, Cristina; León, María; Grau, Oriol; et al. (NeuroImage clinical, 2019)
NIA-AA diagnostic criteria include volumetric or visual rating measures of hippocampal atrophy (HA) as a diagnostic biomarker of Alzheimer's disease (AD). We aimed to determine its utility as a diagnostic biomarker for early onset Alzheimer's disease (EOAD) by assessing Medial Temporal Atrophy (MTA) and hippocampal volume (HV) determination. MTA score and HV quantified by FreeSurfer were assessed in 140 (aged ≤65) subjects with biomarker supported diagnosis: 38 amnesic (A-EOAD), 20 non-amnesic (NA-EOAD), 30 late onset AD (LOAD), 20 fronto-temporal dementia (FTD) and 32 healthy controls (HC). The results showed that the proportion of MTA ≥ 1.5 was higher on LOAD and FTD than EOAD and HC but none of the MTA thresholds (≥1, ≥1.5 and ≥ 2) showed acceptable diagnostic accuracy. LOAD had lower HV than the other groups. A-EOAD HV was lower than NA-EOAD and HC but equal to FTD. The 6258 mm3 cut-off showed good diagnostic accuracy between A-EOAD and HC. Both tools showed a moderate inverse correlation. In conclusion, MTA has a limited diagnostic utility as an EOAD biomarker as it does not discriminate AD from FTD or HC in initial symptomatic stages. HV may discriminate A-EOAD from HC but not from FTD. •FTD had higher MTA scores than AD patients.•MTA scores visual assessment had low diagnostic performance in EOAD.•Amnesic EOAD patients had lower hippocampal volume than the non-amnesic ones.•Quantitative assessment only discriminate between amnesic EOAD from controls.